La fotografía como permanencia de lo efímero en la obra de Edwin Jimeno (2015)
The performance has been conceived and viewed from its inception as an art form, whose main characteristic is the ephemeral nature of their actions, which are known to viewers who are mostly absent from the action, only through photography or videos. Thus, this research aims to investigate the relationship between performative practice as an art form and photography as a practice that not only is projected as documentation and registration, but also in its participation in the performance work in a way that it is much more active, leading artists, such as Edwin Jimeno, to explore other fields that allow them to initiate in processes that until now had not addressed.